Determinants of eczema: population-based cross-sectional study in Germany - Apfelbacher, Christian; Diepgen, Thomas L.; Schmitt, Jochen Maximilian (Allergy, 2011)
Background: Eczema is a chronic inflammatory skin disease and is among the most frequent chronic conditions in childhood and adolescence. It is the aim of this study to investigate determinants of eczema in German children and adolescents. Methods: Data were drawn from the public use files of the German Interview and Examination Survey for Children and Adolescents (KIGGS), a nationwide cross-sectional representative survey conducted between 2003 and 2006, including 17 641 children aged 0-17 (response rate: 66.6%). We investigated the association of a broad set of environmental and lifestyle exposures with ever physician-diagnosed eczema by means of univariable analyses and multivariable logistic regression modelling. Results: The weighted prevalence of ever physician-diagnosed eczema was 13.2% [95% confidence interval (CI) 12.5-13.9%]. In multivariable analysis, significant positive associations of parental allergies (OR 1.94, 95% CI 1.72-2.19), parent-reported infection after birth (OR 1.45, 95% CI 1.05-2.00) and parent-reported jaundice after birth (OR 1.27, 95% CI 1.04-1.54) were revealed. Being a migrant (OR 0.63, 95% CI 0.49-0.80) and keeping a dog (OR 0.78, 95% CI 0.64-0.96) showed significant inverse associations with eczema. Other lifestyle (alcohol consumption during pregnancy) and environmental factors (mould on the walls, pets, origin from East/West Germany) were not significantly related to eczema. Conclusions: This study suggests that a family history of allergies is the strongest determinant of eczema. Perinatal health problems were associated with eczema, pointing to the importance of early life factors in the manifestation of eczema.
First published: 30 August 2010
Gesehen am 07.03.2022